2016
DOI: 10.1159/000448824
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Efficacy of Sofosbuvir Plus Ribavirin in Elderly Patients Infected with Hepatitis C Virus Genotype 2

Abstract: Background: An interferon-free regimen including sofosbuvir and ribavirin (RBV) for patients with hepatitis C virus (HCV) genotype 2 (G2) infection leads to a drastic improvement of sustained virological response (SVR). However, the safety, tolerability, and efficacy in patients aged 75 or older have not been completely understood. Summary: Fifty-six patients with HCV G2 infection who were treated with sofosbuvir and weight-based dose of RBV were enrolled. Thirty-seven patients aged ≥75 and 19 patients aged ≤7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Incidentally, all the few dropouts were attributable to reasons not related to the prescribed therapy. We also consider the safety data of particular significance since this was a frail mostly elderly population, like typical cohorts of cirrhotic patients in the Western world 52,66–68 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidentally, all the few dropouts were attributable to reasons not related to the prescribed therapy. We also consider the safety data of particular significance since this was a frail mostly elderly population, like typical cohorts of cirrhotic patients in the Western world 52,66–68 …”
Section: Discussionmentioning
confidence: 99%
“…We also consider the safety data of particular significance since this was a frail mostly elderly population, like typical cohorts of cirrhotic patients in the Western world. 52,[66][67][68] However, this research reveals also many possible shortcomings. First, the frequency and severity of AE were estimated on the basis of clinical charts and may partially have been classified…”
Section: Lence (≥10%) Also For What Concerns This Ethnicity Mainly In Westernmentioning
confidence: 92%
“…Regarding efficacy, Nishida et al[ 12 ] reported that although the difference was not significant, patients ≥ 75-years-old tended to show a lower SVR rate than patients < 75-years-old (81.3%, 13/16 for patients ≥ 75-years-old; 96.0%, 24/25 for patients < 75-years-old)[ 12 ]. Atsukawa et al[ 11 ] showed SVR rates of 98.1% (51/51) for patients ≥ 75-years-old and 96.8% (211/218) for patients < 75-years-old ( P = 0.999)[ 11 ].…”
Section: Discussionmentioning
confidence: 99%